EXPERIMENTAL DETERMINATION OF THE PARTITIONING BEHAVIOR OF RARE EARTH AND HIGH FIELD STRENGTH ELEMENTS BETWEEN PARGASITIC AMPHIBOLE AND NATURAL SILICATE MELTS - Hilyard M.; Nielsen R.L.; Beard J.S.; Patinõ-Douce A.; Blencoe J. (My University, 2000)
The primary goal of this investigation was to derive a set of expressions that can be used to calculate the amphibole-melt partitioning behavior of the rare earth elements (REE) and the high field strength elements (HFSE) in natural systems. To supplement the existing data set on basaltic systems, we conducted experiments on systems where amphibole was in equilibrium with dacitic, tonalitic and low Si rhyolitic melts. These experiments, doped with La, Sm, Gd, Lu, Ta, Nb, Y, Zr, and Hf, were run at pressures of 2 and 5 kbar, temperatures between 900°C and 945°C, and oxidation conditions ranging from QFM-1 to NiNiO+1.